Effects of storytelling on self-concept, self-esteem and anxiety of children in conflict with the law - Espiritu, Eljielyn C. (2008)
The study aimed to determine the effects of storytelling on the self-esteem, self-concept and anxiety level of the CICL in Molave Youth Homes. It used a quasi-experimental design of pretest and posttest method. Researcher-made materials such as storytelling lesson plans and basic information sheets were also utilized. It was found that CICL perceived themselves as victims of abuse and neglected by their family, peers and society. They sought refuge in peers who experienced the same circumstances. Thus, they develop poor self-concept and self-esteem and very high anxiety level. Some of the participants reported that their self-concept was enriched, their self-esteem enhanced and their anxiety level was lowered through the activities.